Declining Distance Effects in International Trade: Some Country‐Level Evidence. (14th March 2013) - Bleaney, Michael; Neaves, Abelardo S.
Abstract Technical progress can be expected to reduce transport costs over time, yet most studies of bilateral trade based on the gravity model find distance effects to be increasing rather than decreasing. We investigate countries' openness to international trade (the ratio of exports plus imports to GDP). We find that trade decreases with geographical remoteness, land area and lack of access to the sea, all of which are likely to be correlated with transport costs. In contrast to the results obtained with log‐linear models of bilateral trade, distance effects (remoteness and land area) have declined over time. Trade decreases with population density and increases with improvements in the terms of trade, investment and a more liberal trade policy.